2006
DOI: 10.1152/ajpheart.00185.2006
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor- and heparin-dependent regulation of constitutive and agonist-mediated human endothelial barrier function

Abstract: We report functional differences in constitutive and agonist-mediated endothelial barrier function between cultured primary and Clonetics human umbilical vein endothelial cells (pHUVEC and cHUVEC) grown in soluble growth factors and heparin. Basal transendothelial resistance (TER) was much lower in pHUVEC than in cHUVEC grown in medium supplemented with growth factors, such as basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), and human epithelial growth factor (EGF), and heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…We chose TER measurement to assess barrier function because it has been previously established as a reliable index of permeability of vascular endothelial monolayers 9 , which is verified by the fact that the response we observed to VEGF-A reflects previously published findings 8,[14][15][16]31 . TER also has the advantage insofar that rapid, dynamic changes can be measured, whereas solute flux studies are generally less sensitive because they are limited to determining average permeability coefficients over longer time periods required to accumulate enough tracer to accurately measure flux.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We chose TER measurement to assess barrier function because it has been previously established as a reliable index of permeability of vascular endothelial monolayers 9 , which is verified by the fact that the response we observed to VEGF-A reflects previously published findings 8,[14][15][16]31 . TER also has the advantage insofar that rapid, dynamic changes can be measured, whereas solute flux studies are generally less sensitive because they are limited to determining average permeability coefficients over longer time periods required to accumulate enough tracer to accurately measure flux.…”
Section: Discussionsupporting
confidence: 54%
“…We first tested the ability of the endothelial monolayers to respond to VEGF-A (Fig. 2), which increases endothelial permeability both in vivo and in cultured endothelial cell models 8,[14][15][16]31 . In HUVEC monolayers, VEGF-A caused a time-dependent decrease in TER, indicating an opening of the endothelial barrier, followed by a recovery characterized by elevated TER.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized, therefore, that any agent causing an abrupt increase in permeability would likewise trigger an upstream increase in shear rate and subsequent dilation. Figure 8 shows the remote response with histamine and thrombin, each well documented to increase local permeability [33,34]. Figure 8 shows that each agent caused an abrupt increase in upstream velocity and shear rate, which was followed by a remote vasodilation.…”
Section: Resultsmentioning
confidence: 99%
“…These differences probably exist due to donor heterogeneity in HUVEC collection as well as differences in culture conditions. Indeed, Moy et al (2006) described marked differences in functional properties and second messenger activity in HUVEC that were maintained in culture media of varying formulations. Specifically, it was observed that substantial differences existed in the effect of elevated cAMP levels on cell permeability in HUVEC maintained in media recommended by Cambrex Bio Science (as used in the present study) or media less enriched in supplements.…”
Section: Epac1 In a 2b Ar-mediated Erk1/2 Activation In Ec 1197mentioning
confidence: 99%